Paul Tillich’in dini tecrübe anlayışı ve sinemadaki yansımaları - Fidan, Ridade (My University, 2012)
Batı’da son iki yüzyıldır dînî tecrübe din felsefesinde önemli bir problem olarak ele alınmıştır. Bu anlamda Friedrich Schleiemacher, dînî tecrübenin sistematik analizinin öncüsü olarak kabul edilmektedir. Dînî tecrübe meselesinin sistematik olarak ele alınması ile birlikte otoriteci veya akılcı yaklaşımların tersine, dînî tecrübe meselesinde bireyin kişisel tecrübesi, Tanrı inancının meşrûlaştırılması ve Tanrı inancının kanıtı kadar kesin kabul edilmiştir. Öte yandan çağdaş epistemolojide dînî tecrübenin imkânına ve geçerliliğine yönelik önemli eleştiriler ileri sürülmüştür ve dînî tecrübenin empirik verilerinin öznel olması nedeniyle gerekçelendirilemediği iddia edilmiş bu anlamda epistemologlar genel olarak dînî tecrübeyi kültürel bir yapı veya yalnızca bir sosyal fenomen olarak görmüşlerdir. Böyle bir arka planla bu çalışmanın birincil amacı dînî tecrübenin mâhiyetini, dînî tecrübeyi genel terimlerle formüle eden süreçle birlikte açıklamaktır. Bundan sonraki adımda farklı dînî tecrübe yaklaşımlarına (bu tecrübelerin epistemolojik olarak meşrûlaştırılabilir olup olmadığı arasında fark gözetmeksizin) bakılarak dînî tecrübenin mâhiyeti genişletilecektir. Dînî tecrübe ile ilgili bu soruşturmayı genişletmenin yollarından biri de dînî tecrübe problemini kültürün teolojisi bağlamında ele alan Paul Tillich'ten faydalanmaktır. Bu şekilde bir kültür sineması analizi merceğinden bakarak nihâî hakîkatin” dînî tecrübede tezâhürüne bakabileceğiz. Sinema analizi, kültürde “nihâî hakîkatin” tezâhürünü aydınlatmak için Tillich'in ünlü tabloları kullanmasına alternatif ve çağdaş dünyada, daha iyi örnekler sunmaktadır. Bu husûsta bu çalışmanın amacını, kültür teolojisini “nihâî hakîkatin” dînî tecrübede tezâhür etmesi ile ilişkili olarak ele almak oluşturmaktadır ve bu çalışmanın konusu, tartışmalı olan epistemolojik kanıtlama meselelerinden ziyâde dînî tecrübenin günlük hayattaki ve kültürel ifâdelerdeki teolojisi olarak sunulmaktadır. tecrübe” Paul Tillich, “nihâî ilgi”, “korelasyon yöntemi”, “kültür teolojisi”, sinema.

In the last two centuries, religious experience has become an important problem in Western philosophy of religion. Friedrich Schleiermacher pioneered the systematic analysis of religious experience. As opposed to either authority-based or rationalist approaches, here, an individuals’ personal experience is taken as definitive as proof and justification for the belief in God with the systematic analysis of religious experience. At the same time, contemporary epistemology have raised significant criticisms of the possibility and veracity of religious experience due to the fact that the empirical data of religious experience is subjective and for this reason cannot be justified and therefore that they generally see religious experience as cultural construct or merely a social phenomenon. With this background, this dissertation’s primary aim is to explain the content of the religious experience with the process that formulate religious experience in general terms. Then, will broaden the “content” of religious experience, by looking at all claimed religious experiences whether these claims can be epistemologically justified or cannot be justified. One way to expand this investigation is to draw upon the work of Paul Tillich, who understands the problem of religious experience in the context of theology of culture. This allows us to look at, in particular, the manifestation of “ultimate reality” through religious experience through the lens of an analysis of a culture’s cinema. We argue that film analysis provide alternative and in the contemporary world, better examples than Tillich’s use of painting to illustrate the manifestation of ultimate reality in a culture. The aim of this work is to focus on ultimate reality manifesting itself in religious experience with it's relation to cultural theology, so that the attention shifts from problematic epistemological issues of justification to the theology of religious experience in daily life and cultural expressions. KEY WORDS: “religious experience”, Paul Tillich, “ultimate concern” , “method of correlation”, “theology of culture”, cinema.
Keywords: Sinema